Handbook of mindfulness theory, research, and practice - Brown, Kirk Warren; Creswell, J. David; Ryan, Richard M. (New York The Guilford Press, 2015)
"While we have learned a great deal about mindfulness in the past 30 years, unquestionably the field of mindfulness science is still maturing, and in the chapters herein the authors have taken pains to point out how the current research is limited in its methods and conclusions, and have pointed to specific ways in which future research studies can overcome these limitations. That said, the work represented in this Handbook is among the best conducted to date, measured in terms of scientific creativity, sophistication, and insight. Our hope is that this volume offers readers both a panoramic view of the current science of mindfulness and a compass to help guide its ongoing evolution"--Provided by publisher.
Machine generated contents note: 1. Introduction: The Evolution of Mindfulness Science, Kirk Warren Brown, J. David Creswell, & Richard M. Ryan -- I. Historical and Conceptual Overview of Mindfulness -- 2. Buddhist Conceptualizations of Mindfulness, Rupert Gethin -- 3. Developing Attention and Decreasing Affective Bias: Toward a Cross Cultural Cognitive Science of Mindfulness, Jake H. Davis & Evan Thompson -- 4. Reconceptualizing Mindfulness: The Psychological Principles of Attending in Mindfulness Practice and Their Role in Well Being, James Carmody -- II. Mindfulness in the Context of Contemporary Psychological Theory -- 5. Mindfulness in the Context of the Attention System, Yi Yuan Tang & Michael I. Posner -- 6. Mindfulness in the Context of Processing Mode Theory, Edward R. Watkins -- 7. Being Aware and Functioning Fully: Mindfulness and Interest-Taking within Self Determination Theory, Edward L. Deci, Richard M. Ryan, Patricia P. Schultz, & Christopher P. Niemiec -- 8. Mindfulness in Contextual Cognitive Behavioral Models, Thomas G. Szabo, Douglas M. Long, Matthew Villatte & Steven C. Hayes -- III. The Basic Science of Mindfulness -- 9. From Conceptualization to Operationalization of Mindfulness, Jordan T. Quaglia, Kirk Warren Brown, Emily K. Lindsay, J. David Creswell, & Robert J. Goodman -- 10. The Neurobiology of Mindfulness Meditation, Fadel Zeidan -- 11. Cognitive Benefits of Mindfulness Meditation, Marieke K. van Vugt -- 12. Emotional Benefits of Mindfulness, Joanna J. Arch & Lauren N. Landy -- 13. The Science of Presence: A Central Mediator of the Interpersonal Benefits of Mindfulness, Suzanne C. Parker, Benjamin W. Nelson, Elissa S. Epel, & Daniel J. Siegel -- 14. Did the Buddha Have a Self?: No Self, Self, and Mindfulness in Buddhist Thought and Western Psychologies, Richard M. Ryan & C. Scott Rigby -- IV. Mindfulness Interventions for Healthy Populations -- 15. Mindfulness Based Stress Reduction for Healthy Stressed Adults, Shauna L. Shapiro & Hooria Jazaieri -- 16. Mindfulness Training for Children and Adolescents: A State-of-the-Science Review, David S. Black -- 17. Mindfulness Training to Enhance Positive Functioning, Kirk Warren Brown -- V. Mindfulness Interventions for Clinical Populations -- 18. Mindfulness Interventions for Emotion Dysregulation Disorders: From Self Control to Self Regulation, Thomas R. Lynch, Sophie A. Lazarus, & Jennifer S. Cheavens -- 19. Mindfulness Based Cognitive Therapy for Chronic Depression, Julie Ann Irving, Norman A. Farb, & Zindel V. Segal -- 20. Mindfulness in the Treatment of Anxiety, Sarah A. Hayes Skelton & Lauren P. Wadsworth -- 21. A Mindfulness Based Approach to Addiction, Sarah Bowen, Cassandra Vieten, Katie Witkiewitz, & Haley Douglas -- 22. Mindfulness Based Interventions for Physical Conditions: A Selective Review, Linda E. Carlson -- 23. Biological Pathways Linking Mindfulness with Health, J. David Creswell.
Includes bibliographical references and index.
Keywords: Attention; Awareness; Meditation -- Therapeutic use